Prognostic value of neutrophil-to-lymphocyte ratio for nasopharyngeal carcinoma: A meta-analysis. Issue 29 (July 2017) - Yin, Jun; Qin, Yuan; Luo, Yu-kun; Feng, Mei; Lang, Jin-yi
Abstract: Background: The prognostic value of the neutrophil-to-lymphocyte ratio (NLR) for nasopharyngeal carcinoma (NPC) remains controversial. This study was designed to provide a more accurate assessment of the prognostic value, based on a meta-analysis. Methods: A comprehensive search for relevant studies published before June 2016 was performed using the PubMed, Cochrane Library, and Web of Science databases. The correlations of NLR with overall survival (OS) and progression-free survival (PFS) were evaluated for NPC. Hazard ratios (HRs) and associated 95% confidence intervals (CIs) were calculated to estimate the effects. Results: Six studies with a total of 4359 NPC patients were included in this meta-analysis. The pooled results showed that, among patients with NPC, elevated pretreatment NLR was associated with poorer OS (HR = 1.74, 95% CI = 1.45–2.10) and PFS (HR = 1.48, 95% CI = 1.30–1.69). Subgroup analyses indicated that the use of different cut-off values for NLR (<3 or ≥3) did not affect the consistent prognostic value of NLR for OS or PFS. No significant heterogeneity or publication bias was observed among the included studies for OS or PFS ( P > .05). Conclusions: This meta-analysis indicates that elevated pretreatment NLR might be a valuable predicative biomarker of poor prognosis for patients with NPC.